Rethinking Gender In Islamic Law - Suud Sarim Karimullah; Mukhid; Zumiyati Sanu Ibrahim; Muhajir (Sunan Kalijaga State Islamic University & The Asia Foundation, 2024)
In the study of feminist hermeneutics, gender construction in Islamic law tries to bridge the gap between the dominant patriarchal norms in interpreting traditional Islamic law and modern society regarding gender equality for social justice. By exploring the classical literature and contemporary Islamic legal text, this study focuses on the problems of gender construction through the lens of feminist hermeneutics in Islamic law. The pattern in this feminist hermeneutic approach not only expands but also deepens the understanding of paradigmatic changes in gender construction in the framework of Islamic law. This perspective introduces a new idea for exploring gender construction within the legal framework. This approach challenges the dominant patriarchal interpretation of Islamic law, particularly women's roles and rights. This social change can be perceived in an inclusive view more responsive to gender issues.[ Dalam kajian lensa hermeneutika feminis, konstruksi gender dalam hukum Islam berupaya menjembatani kesenjangan antara norma-norma dominan patriarki dalam interpretasi hukum Islam tradisional dan tuntutan masyarakat modern dalam kesetaraan gender demi keadilan sosial. Dengan menggali sumber pustaka teks-teks hukum Islam klasik dan kontemporer maupun literatur akademik yang relevan, paper ini mengulas lebih lanjut permasalahan kostruksi gender dalam kacamata hermeneutika feminis pada hukum Islam. Pola kajian dalam pendekatan hermeneutika feminis ini tidak hanya memperluas tetapi memperdalam pemahaman perubahan paradigmatik konstruksi gender dalam kerangka hukum Islam. Penerapan perspektif ini membuka wilayah baru bagi eksplorasi konstruksi gender dalam kerangka hukum tersebut. Pendekatan ini menantang fondasi interpretasi patriarkal yang dominan dalam hukum Islam, khususnya terkait peran dan hak-hak perempuan. Perubahan sosial terlihat dalam pandangan inklusif yang lebih responsif terhadap isu gender.]